2012
DOI: 10.1002/ptr.4697
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic and Spermatogenic Activity of Alkylamide‐Rich Ethanol Solution Extract of Anacyclus pyrethrum DC

Abstract: Anacyclus pyrethrum (A. pyrethrum) has been used as Vajikaran Rasayana (aphrodisiac) in traditional Indian ayurvedic medicine to treat male sexual dysfunction, including infertility. Aphrodisiac activity may be due to an increase in the production or effect of androgens, so this study sought to evaluate the androgenic and spermatogenic potential of the alkylamide-rich ethanol solution extract. Male Wistar strain rats weighing between 150 and 180 g were completely randomized divided into five groups. The ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…Administration of alkamide-rich extracts of A. pyrethrum showed improvement in sexual behavior of male rats. With respect to the similar properties observed in L. meyeni the authors suspected the presence of pellitorine (101a) as possible contributor to these effects and hypothesized that alkamides may mimic the action of testosterone or stimulate secretion of testosterone that improves sexual function (Sharma et al , 2013. Similar effects on sexual behavior in male rats were detected in the ethanolic flower extract of Acmella paniculata.…”
Section: Miscellaneous Propertiesmentioning
confidence: 82%
“…Administration of alkamide-rich extracts of A. pyrethrum showed improvement in sexual behavior of male rats. With respect to the similar properties observed in L. meyeni the authors suspected the presence of pellitorine (101a) as possible contributor to these effects and hypothesized that alkamides may mimic the action of testosterone or stimulate secretion of testosterone that improves sexual function (Sharma et al , 2013. Similar effects on sexual behavior in male rats were detected in the ethanolic flower extract of Acmella paniculata.…”
Section: Miscellaneous Propertiesmentioning
confidence: 82%
“…Additional study further demonstrated the androgenic potential and increased sperm quality (sperm count, motility and viability) along with the fertilising capacity of the semen sample of rats treated with ethanol extract of A. pyrethrum after 28 days of treatment (Sharma et al, 2013). Other effects caused by the ethanol-rich extract include increased weight of the testis and accessory sex glands (prostate, seminal vesicles and epididymis) and spermatogenic activities and reproductive hormone (luteinising hormone and follicle-stimulating hormone) concentrations (Sharma et al, 2013). The aqueous extract of the roots of A. pyrethrum also has the capacity to improve the sexual behaviour of treated rats along with pronounce anabolic and spermatogenic effects.…”
Section: Anac Yclus Pyre Thrummentioning
confidence: 87%
“…The petroleum ether extract of A. pyrethrum was shown to increase the penile erection index, mount and intromission frequency along with decreased mount latency, intromission latency period of male rats (Sharma et al, ). Additional study further demonstrated the androgenic potential and increased sperm quality (sperm count, motility and viability) along with the fertilising capacity of the semen sample of rats treated with ethanol extract of A. pyrethrum after 28 days of treatment (Sharma et al, ). Other effects caused by the ethanol‐rich extract include increased weight of the testis and accessory sex glands (prostate, seminal vesicles and epididymis) and spermatogenic activities and reproductive hormone (luteinising hormone and follicle‐stimulating hormone) concentrations (Sharma et al, ).…”
Section: Anacyclus Pyrethrummentioning
confidence: 95%
“…Testosterone is the key hormone responsible for regulating spermatogenesis (Dirican and Kalender, 2012), together with maintaining the blood-testis barrier and, supporting the completion of meiosis and spermiation (Mihalik et al, 2015). Importantly, fructose synthesis and secretion is dependent on the secretion of testosterone (Sharma et al, 2013). As noted above, optimal spermatogenesis is a result of the comprehensive effect of hormonal regulation.…”
Section: Discussionmentioning
confidence: 99%